Efektivitas Model Concept Sentence Berbantuan Media Kuartet Terhadap Keterampilan Menulis Teks Deskripsi Kelas IV Sekolah Dasar - Restu Amalia Istiqomah; Yeni Dwi Kurino; Wina Dwi Puspitasari (Journal on Education, 2024)
This research was motivated by the low writing skills of descriptive text among fourth-grade students. The purpose of this study was to determine the effectiveness of the Concept Sentence model assisted by quartet media on the skills of writing descriptive texts. The research method used was a quasi-experimental design with a non-equivalent control group design. The research sample was 23 students in class IVA as the experimental class and 23 students in class IVB as the control class. The data collection techniques in this study were written tests and non-tests. The data analysis technique used t-test and N-Gain. The analysis results show that (1) there is a difference in the average writing skills of descriptive text before and after being treated with an obtained significance value of 0.000 < 0.05, meaning that Ho is rejected and Ha is accepted, (2) there is a significant increase in the class that was treated by 84% in the high category. It was concluded that the Concept Sentence model assisted by Quartet Media is effective for Descriptive Text Writing Skills in fourth-grade elementary school.